Integrating Associative Rule-Based Categorization with Econometric Modelling for Analysis of Barriers and Advantages in Cloud Solutions Absorption in Manufacturing - Witold BARTKIEWICZ; Beata GONTAR; Zbigniew GONTAR (Communications of International Proceedings, 2021)
The aim of this paper is to investigate the structure of the knowledge and factors affecting the awareness of managers (experts in the field) of manufacturing enterprises in Poland, as to the benefits and barriers resulting from the adoption of cloud computing solutions. In the study four input factors were considered: company size, strategic maturity of the organization, structure of the capital (domestic or international) and the practical experiences with cloud solutions implementation. A comprehensive survey was carried out in 2018, for representative sample about 400 industrial enterprises. The influence of the studied factors on expert’s opinions was examined, using weighted least-squares econometric analysis for categorical data and association mining a priori algorithm.
Keywords: Cloud Computing; Association Analysis; Weighted Least Squares Analysis Of Categorical Data; Technology Adoption